An Investigation Into Collocation Of Nouns Concerning Food And Beverage In English And Vietnamese - Nguyễn Thị Kiều Xuân (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims at investigating the syntactic and semantic features of collocation of nouns concerning food and beverage in English and Vietnamese. The study finds out the use of collocation of nouns concerning food and beverage. The study is conducted through the adoption if descriptive, quantitative, qualitative and contrastive approaches. The data collection of 500 English samples and 500 Vietnamese ones randomly gathered from various websites. The most important and noteworthy aspect of the study is the similarities and differences between English and Vietnamese collocation of nouns concerning food and beverage, which are given so as to provide learners with better use of language in communication. The findings of the study point out a variety of syntactic and semantic features of collocation of nouns concerning food and beverage. Then, some implications for teaching and learning collocation of nouns concerning food and beverage are suggested, and for further study as well.